Health cyberactivists: the multiple young friends for sclerosis (Práxis Educativa, 2019)
This article tries to understand the subjectivation movement of a group of young cyberactivists diagnosed with Multiple Sclerosis that are investing in the change of the illness’ social meaning and of the patient’s identity. Their actions are online, but they also act in physical bodies of public health policy decisions. According to Tourette-Turgis (2013), we acknowledge the narrative of these young people, who, before the illness’ diagnosis, search and organize knowledge about themselves or a (self-)developing process of learning with the illness. With Malini and Antoun (2013), we try to understand the cyberspace as a rhizome in which multiple articulations multiply about health/illness as well as a new profile of the social movements and non-governmental organizations. These subjectivations are paraphrases of domination systems moderately known, but, overall, to new regulations in friendship processes as a path to self-care (FOUCAULT, 2004). Keywords: Narratives. Subjectivities. Cyberactivisms.